1995
DOI: 10.1002/cne.903600205
|View full text |Cite
|
Sign up to set email alerts
|

Müller glial cells of the tree shrew retina

Abstract: The tree shrew is one of the few mammalian species whose retinae are strongly cone dominated, which is usually the case in reptilian and avian retinae. Müller cells of the tree shrew (Tupaia belangeri) retina were studied by transmission electron microscopy of tissue sections and freeze-fracture replicas, by immunolabeling of the intermediate filament protein vimentin in radial paraffin sections and in whole retinae, as well as by intracellular dye injection in slices of retinae. In addition, enzymatically iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
3
18
0
1
Order By: Relevance
“…2). The dark appearance of the cytoplasm of Mu$ ller cells represents a reliable criterion for their ultrastructural identification that has already been applied, by others, to Tupaia belangeri (Reichenbach et al 1995) as well as many other species (Holla$ nder et al 1991 ;Ramirez et al 1996). We never observed cell processes revealing transitions between electron-dense and electron-lucent cytoplasm.…”
Section: supporting
confidence: 55%
See 1 more Smart Citation
“…2). The dark appearance of the cytoplasm of Mu$ ller cells represents a reliable criterion for their ultrastructural identification that has already been applied, by others, to Tupaia belangeri (Reichenbach et al 1995) as well as many other species (Holla$ nder et al 1991 ;Ramirez et al 1996). We never observed cell processes revealing transitions between electron-dense and electron-lucent cytoplasm.…”
Section: supporting
confidence: 55%
“…In Tupaia, the distribution of retinal macroglial cells (Reichenbach et al 1995 ;Knabe & Ochs, 1999) conforms to the basic mammalian pattern : the occurrence of astrocytes is restricted to the inner parts of the retina, whereas Mu$ ller cells extend throughout the entire depth of the retina (Chan-Ling, 1994). The present stereological study demonstrates that, in Tupaia, the contribution of Mu$ ller cells to the investment of retinal capillaries is distinctly different among the 3 outermost capillary layers studied.…”
Section: mentioning
confidence: 89%
“…The authors concluded that "Müller cells share the ability of astrocytes to induce the formation of barrier properties by vascular endothelial cells" and might, therefore, contribute to the formation of the inner blood-retina barrier (Tout et al 1993). Reichenbach et al (1995) provided the first detailed report of the structure and distribution of Müller cells in the retina of the tree shrew Tupaia belangeri. Tree shrews are basal eutherian mammals and their relationship to primates is under debate (Wible and Zeller 1994).…”
Section: Introductionmentioning
confidence: 98%
“…Tree shrews are basal eutherian mammals and their relationship to primates is under debate (Wible and Zeller 1994). Reichenbach et al (1995) have noted that, in Tupaia, "wherever blood vessels crossed through the INL (inner nuclear layer) or IPL (inner plexiform layer), they were surrounded by lamellar extensions of Müller cells". However, these authors did not focus on the structural properties of the inner blood-retina barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture media and supplements were from Invitrogen (Karlsruhe, Germany). Primary rat Müller cells and mouse RGCs were isolated and cultured as previously described [14,35]. Briefly, retinae from six-to nine-day-old Long-Evans rats were isolated and mechanically dissociated by careful homogenization.…”
Section: Animals and Cell Culturesmentioning
confidence: 99%